Percolation and criticality in a mitochondrial network - Aon, Miguel A. (National Academy of Sciences, 2004)
Synchronization of mitochondrial function is an important determinant of cell physiology and survival, yet little is known about the mechanism of interorganellar communication. We have recently observed that coordinated cell-wide oscillations in the mitochondrial energy state of heart cells can be induced by a highly localized perturbation of a few elements of the mitochondrial network, indicating that mitochondria represent a complex, self-organized system. Here, we apply percolation theory to explain the mechanism of intermitochondrial signal propagation in response to oxidative stress. A global phase transition (mitochondrial depolarization) is shown to occur when a critical density of mitochondria accumulate reactive oxygen species above a threshold to form an extended spanning cluster. The scaling and fractal properties of the mitochondrial network at the edge of instability agree remarkably well with the idea that mitochondria are organized as a percolation matrix, with reactive oxygen species as a key messenger.